Gender and IR in the MENA Region: The Role of Arab Women’s Diplomacy in Peacebuilding, Decision Making, and Conflict Resolution (Journal of Advanced Research in Social Sciences, 2023)
This research studies gender and international relations in the MENA region. It scrutinises the Arab women’s role and representation in diplomacy and foreign affairs. The study aims to examine the status of women diplomats in the region and identify the necessary strategies and recommendations to promote their role in IR. It provides an overview of Arab women’s diplomacy, the progress made, and the challenges women continue to face in international relations. It highlights why and how women are underrepresented in MENA diplomacy, how women’s engagement enhances diplomacy in the region, and strategies for future gender diplomacy. The study develops a new application of the Feminist IR theory to the Arab IR and demonstrates the relevance of this approach to new diplomatic and political contexts. Exploring gendered institutional practises and hierarchies in MENA foreign policy, the survey offers insights into perspectives previously marginalised in core concepts of MENA IR, beyond traditional courtesy diplomacy. It focuses primarily on women in IR positions and their contributions to peacebuilding, decision making and conflict resolution. The research uses a mixed-method-approach consisting of a quantitative data analysis of IR international documents and policy reports, and a qualitative survey of Arab women diplomats, both official and unofficial. The objective of the qualitative survey is to explore women diplomats’ perceptions of their status, the challenges they face, and their recommendations for better female diplomacy. The study found that MENA IR is gendered and women are underrepresented in Arab diplomacy, that the underrepresentation of women is due to social and ideo-cultural factors, that the few women diplomats promote diplomacy in the region, and that future strategies should be implemented to bridge the gap in gendered IR.